Covert oculo-manual coupling induced by visually guided saccades - Falciati, Luca; Gianesini, Tiziana; Maioli, Claudio (Frontiers in Human Neuroscience, 2013)
Hand pointing to objects under visual guidance is one of the most common motor behaviors in everyday life. In natural conditions, gaze and arm movements are commonly aimed at the same target and the accuracy of both systems is considerably enhanced if eye and hand move together. Evidence supports the viewpoint that gaze and limb control systems are not independent but at least partially share a common neural controller. The aim of the present study was to verify whether a saccade execution induces excitability changes in the upper-limb corticospinal system (CSS), even in the absence of a manual response. This effect would provide evidence for the existence of a common drive for ocular and arm motor systems during fast aiming movements. Single-pulse TMS was applied to the left motor cortex of 19 subjects during a task involving visually guided saccades, and motor evoked potentials (MEPs) induced in hand and wrist muscles of the contralateral relaxed arm were recorded. Subjects had to make visually guided saccades to one of 6 positions along the horizontal meridian (±5°, ±10° or ±15°). During each trial, TMS was randomly delivered at one of 3 different time delays: shortly after the end of the saccade or 300 ms or 540 ms after saccade onset. Fast eye movements towards a peripheral target were accompanied by changes in upper-limb CSS excitability. MEP amplitude was highest immediately after the end of the saccade and gradually decreased at longer TMS delays. In addition to the change in overall CSS excitability, MEPs were specifically modulated in different muscles, depending on the target position and the TMS delay. By applying a simple model of a manual pointing movement, we demonstrated that the observed changes in CSS excitability are compatible with the facilitation of an arm motor program for a movement aimed at the same target of the gaze. These results provide evidence in favor of the existence of a common drive for both eye and arm motor systems.